Kesiapan Karir Siswa Mathayom Tasdikiah School dan Siswa MA Mutma’inah Cibinong Indonesia: Studi Komparasi Thailand dan Indonesia - Kaysul Fathiin; Imas Kania Rahman; Putri Ria Angelina (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze and compare the career readiness of Mathayom 5 Tasdikiah School students in Songkhla, Thailand and 11th grade students of MA Mutma’inah Cibinong, Indonesia. This study uses a quantitative approach with a comparative design. The research sample consisted of 110 students consisting of 55 students from each school selected using a specific sampling technique. The research data were collected through a Likert-scale career readiness questionnaire and analyzed using descriptive statistics and the Mann-Whitney U difference test. The results showed that the career readiness of Tasdikiah School students was mostly in the high category with a percentage of 52.7%, while the career readiness of MA Mutma’inah students was mostly in the low category with a percentage of 60.0%. However, the results of the Mann-Whitney U test showed an Asymp. Sig. value of 0.392 (p > 0.05), so there was no significant difference in career readiness between the two groups of students. This finding indicates that differences in school and country contexts have not resulted in statistically significant differences in career readiness levels, so it is necessary to strengthen career development programs that are appropriate to the needs of students in each school.